The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/1759-7714.13800
|View full text |Cite
|
Sign up to set email alerts
|

Plasma miR‐1247‐5p, miR‐301b‐3p and miR‐105‐5p as potential biomarkers for early diagnosis of non‐small cell lung cancer

Abstract: Background Accumulating evidence shows that microRNAs are aberrantly expressed and exert essential roles in the tumorigenesis and tumor progression of non‐small cell lung cancer (NSCLC). Methods The plasma miRNAs from five healthy donors and four NSCLC patients were profiled by miRNA microarray. The differentially expressed miRNAs from 154 primary NSCLC patients and 146 healthy donors were subjected to RNA isolation and verified by quantitative PCR (qPCR). Results The miRNA microarray analysis revealed that 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 30 publications
3
15
0
Order By: Relevance
“…Many of the miRNAs, which we detected as significantly regulated in melanoma, are already described in the literature as relevant for the development of other cancers [69,70] or are known to be dysregulated in melanoma, but without a distinctly described molecular function [17,71]. The analysis of their potential target genes and involved pathways in our study allows interesting conclusions to be drawn about their role in melanoma tumorigenesis.…”
Section: Discussionsupporting
confidence: 56%
“…Many of the miRNAs, which we detected as significantly regulated in melanoma, are already described in the literature as relevant for the development of other cancers [69,70] or are known to be dysregulated in melanoma, but without a distinctly described molecular function [17,71]. The analysis of their potential target genes and involved pathways in our study allows interesting conclusions to be drawn about their role in melanoma tumorigenesis.…”
Section: Discussionsupporting
confidence: 56%
“…21 Of note, circulating miR-105-5p might serve as a diagnostic or prognostic biomarker for non-small cell lung cancer or triple negative BC. 22,23 These studies support our findings that miR-105-5p may be related to GI and has the potential as a biomarker for cancer. Upregulation of miR-767-5p was associated with poor prognosis and disease progression in hepatocellular carcinoma.…”
Section: Discussionsupporting
confidence: 86%
“… 30 , 31 A high plasma miR-105 level resulted in poor prognosis of NSCL and was a potential biomarker for early diagnosis of NSCL. 32 In addition, miR-105 was inhibited by LINC00261 and affected the metastasis and proliferation of NSCLC. 33 Consistent with previous reports, our results revealed that miR-873 and miR-105-2 shorten the survival time of LUAD patients by altering the relative proportions of TICs in the TME.…”
Section: Discussionmentioning
confidence: 99%